MEMBANGUN KEPEMIMPINAN MELALUI PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Maharani, Nuralda Haslita; L, Nurlian Sriyunianti; Margawati, Langgeng Arta (Universitas Sulawesi Tenggara, 2023)
Character education in elementary schools plays an important role in building basic leadership values in students. This study aims to analyze how character education can help shape leadership at the elementary school level. Through a literature study approach, this study explores various concepts and practices of character education that can be applied in elementary schools to develop leadership qualities. The results of the study indicate that character education integrated into the learning process can build a foundation for leadership that focuses on developing students' character, responsibility, empathy, and social skills. Education based on moral values such as honesty, cooperation, and justice will form leaders who are responsible and have integrity.